Sains Islam Berbasis Nalar Ayat-ayat Semesta - Azaki Khoirudin (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2017)
This study aims to examine the paradigm of Islamic Science based on the logic of the universal verses. Using the literature research method, qualitative research approach and philosophical analysis. Interaction between religion and science can be seen through several perspectives that include Islamization of science, Islamic scientification, Integration of interconnection (paradigm of Indonesian science). While science-based Al-Qur'an can be divided into three, namely Modern Science, Islamic Science and the logic of the universal verses. This study also found that Islamic Science can be built from the Qur'an as the basis of scientific epistemology. Revelation as a source that provides inspiration for the construction of science. This new Ijtihad is a project of civilization and progress of Islam, because it awakens to Muslims about the importance of kauniyah verses that have been forgotten. The logic of the universal verses proposes an